Association between prognostic biomarkers of CyclinD1 and estrogen receptor in breast cancer by immunohistochemical analysis - Aung, Sanda; Aung, Tha (2013)
Breast cancer is the most common malignant tumour & the leading cause of cancer death in women worldwide annually. Invasive duct carcinoma of the breast is a clinically and biologically heterogeneous disease. A cross–sectional study was carried out among 40 cases of formalin fixed, paraffin embedded tissue sections of invasive duct carcinoma (NST) of the breast. Histological grading was done according to Modified Bloom and Richardson Grading. Immunoexpression of cyclinD1 (using DAKO M7155) and ER (using DAKO M7047) were detected by immunohistochemistry. In this study, at least 10% of brown nuclear staining regardless of staining intensity was interpreted as positive. The data was analysed by using chi- square test. (SPSS version 11.5) . In 40 patients, the ages ranged from 34 to 78 years with a mean of 54 years. CyclinD1 expression was detected in 43% (17 of 40) of cases, and was inversely associated with histological grade (p=0.01). ER immunoreactivity was found in 30% (12 of 40) of patients and was inversely associated with histological grade (p=0.021). CyclinD1 immunoreactivity was positively associated with estrogen receptor expression (p=0.043). There was no significant correlation with clinical prognostic parameters of age, menopausal status, tumour size and clinical stage with both prognostic biomarkers.